MANAJEMEN MOTIVASI KINERJA GURU, KEPEMIMPINAN KEPALA SEKOLAH, DAN PENDAMPINGAN INSTRUKTUR KABUPATEN UNTUK MENINGKATKAN IMPLEMENTASI PERUBAHAN KURIKULUM 2013 REVISI 2017 (Kajian Analisis Kualitatif di SMP Bahrul Ulum Kota Tasikmalaya, dan di SMPN 1 Sukadana Kabupaten Ciamis) - Rosida Amalia; E. Mulyasa; Yosal Iriantara (Media Nusantara, 2019)
This research rationalization is curriculum changing of 2013 Curriculum 2016revision according to Permendikbud number 20, 21, 22 and 23. The main factorwhich observed is human resources improvement, the teacher, the headmaster’sleadership and the supervision of regency’s instructor. The teacher factor whichsupport the changing includes motivation. The motivation management of teacher’sperformance consist of primary and secondary necessity’s fulfillment. The researchresult shows the implementation of teacher’s motivation technique performancecan improve the Curriculum 2013 changing 2017 revision in Bahasa Indonesiasubject. In the CBAM dimension changing stages, SMP Bahrul Ulum reaches Consequen phase while SMPN 1 Sukadana reaches Collaboration phase. In LoU stages, SMP Bahrul Ulum reaches IVA routine, while SMPN 1 Sukadana reaches IV B phase. According to the research result, the description of implementation Curriculum 2013 changing 2017 revision, smp Bahrul Ulum just reaches Cooptation phase, the situation of realization modifying programme or new practice. While SMPN 1 Sukadana is going to Mutual Adoption phase.